Implementing Provisions on Social Protection of Enterprise Personnel in accordance with the National Standards on Accounting and IFRS - N. V. Ovsiuk; I.I. Аfanasieva (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2025)
The article highlights the social protection scheme for enterprise personnel in Ukraine, involving the assistance through mandatory state social insurance and employing social policy instruments adopted at a specific enterprise. The demographic situation in Ukraine does not allow for a decent standard of living for citizens after the end of their working life, which necessitates the comprehensive development of the national pension system encompassing the accumulative pension system and pension provision through other-than-state channels, e.g. non-state pension funds (NPFs). The development of pension systems and pension provision schemes in foreign countries was analyzed. It was demonstrated that the non-state pension provision was a factor underlying the successful development of a market-economy country, because the financial resources invested in NPFs, apart from bringing a stable income to the personnel after the end of their working life, would work for the benefit of the national economy, returning to enterprises in the form of investment capital. The data on implementing the social protection of Ukrainian employees is accounted and reported in compliance with methodologies contained in National Standards on Accounting and IFRS. An important source of information about the development of non-state pension provision is the accounting system of an insured enterprise, accumulating and storing detailed data on the types of expenses on the social security of personnel. However, the national accounting legislation currently lacks a separate standard for pension programs to be used in the compilation of financial reporting on these programs. The authors proposed a draft standard for accounting and reporting on pension programs, designed to improve the financial reporting of NPFs for the purposes of managing their assets and increasing their profitability.